Lipid nanocarrier containing eugenol for denture hygiene: evaluation of efficacy against Candida biofilms - Irisvaldo Lima GUEDES; Matheus Oliveira do NASCIMENTO; Leandro de Sousa DIAS; Alyne Rodrigues de ARAUJO-NOBRE; Humberto Medeiros BARRETO; Érika de Araújo ABI-CHACRA; Ana Cristina Vasconcelos FIALHO; Gláuber Campos VALE; André Luis Menezes CARVALHO (Journal of Applied Oral Science)
Abstract Eugenol has demonstrated efficacy against Candida spp., which is highly prevalent in denture wearers. However, the low water solubility and high volatility limit its application. The encapsulation in nanostructured lipid carriers (NLCs) may be a viable approach for developing new sanitizing agents for denture hygiene. Objective To develop a sanitizing dispersion for denture hygiene using nanostructured lipid carriers (NLCs) containing eugenol and to evaluate the efficacy against Candida spp. biofilms. Methodology The formulation was prepared using the ultrasonication method and characterized in terms of particle size (PS), polydispersity index (PDI), zeta potential (ZP), and encapsulation efficiency (EE). The minimum inhibitory concentration (MIC) was determined by the broth microdilution method and the antifungal activity was evaluated by four treatment groups (nanostructured formulation containing eugenol (NFE), free eugenol (FE), saline solution (SS), and the drug-free formulation NFW after eight hours of immersion in biofilms of two Candida species (Candida albicans and Candida glabrata) adhered to polymethyl methacrylate resin specimens. Results The nanoparticles of NFE showed a particle size of 199.5±2.55 nanometers (nm) as measured by DLS, high homogeneity (0.07±0.02), an EE of 83.07±0.23, and a negative ZP (-25.86±0.65). The MICs of FE for Candida albicans and Candida glabrata were up to 10 times (64 µg/mL) and eight times (128 µg/mL) higher, respectively, than the MICs of NFE (6 µg/mL and 16 µg/mL). The biofilms of these microorganisms showed a significant reduction after immersion in NFE compared to the other tested groups (FE, NBF, and SS) (P<0.0001). Conclusion The NFE demonstrated fungicidal activity against the isolated strains and significantly reduced Candida biofilms, thus showing promising performance for the sanitization of dentures over eight hours.